Determinan Kejadian Dermatitis pada Nelayan di Dusun Waemital, Negeri Pelauw - Suryanti Tukiman; Rahma Tunny; Ety Dusra; Abd Rijali Lapodi; Mariene Wiwin Dolang; Dasmawati Sampolawa (Wiraraja Medika : Jurnal Kesehatan, 2026)
Dermatitis is one of the most common occupational skin diseases among fishermen due to exposure to seawater, humid working environments, and low use of personal protective equipment (PPE). Data from the Pelauw Health Center indicate that dermatitis cases remain relatively high. The occurrence of dermatitis is influenced by several factors, including age, history of allergies, personal hygiene, and use of PPE. This study aimed to determine the determinants of dermatitis among fishermen in Waemital Hamlet, Pelauw Village, Pulau Haruku District, Central Maluku Regency in 2025. This study employed a quantitative method with an analytical observational design using a cross-sectional approach. The study population consisted of all fishermen in Waemital Hamlet, totaling 35 respondents, using a total sampling technique. Data were collected using a structured questionnaire covering age, history of allergies, personal hygiene, use of PPE, and dermatitis occurrence. Data analysis was performed using univariate and bivariate analysis with the Chi-Square test at a significance level of α = 0.05. The results showed that most respondents had dermatitis (85.7%), had a history of allergies (77.1%), did not use PPE (91.4%), and had poor personal hygiene (54.3%). The bivariate analysis showed no significant relationship between age and dermatitis occurrence (p = 1.000) or between history of allergies and dermatitis occurrence (p = 0.067). In contrast, there was a significant relationship between personal hygiene and dermatitis occurrence (p = 0.006), as well as between PPE use and dermatitis occurrence (p = 0.047). It can be concluded that personal hygiene and PPE use are factors associated with dermatitis among fishermen, while age and history of allergies are not significantly related. Improvement in clean and healthy living behavior and consistent use of PPE is needed to reduce the risk of dermatitis among fishermen.